Asuhan Keperawatan pada Pasien PPOK (Penyakit Paru Obstruktif Kronik) dengan Masalah Ketidakefektifan Bersihan Jalan Napas - Dunggio, Abdul Rivai Saleh; Aryadi, Anggi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a pathological lung condition characterized by progressive and not fully reversible airflow obstruction. One of the main nursing problems that often arises is ineffective airway clearance due to accumulation of secretions. This study aims to describe the nursing care process for COPD patients with a focus on interventions for ineffective airway clearance. The method used is a descriptive case study with a nursing process approach. The results show that interventions such as effective coughing techniques, positional therapy, and adequate hydration can increase the effectiveness of airway clearance. The conclusion of this study is the need for a holistic and sustainable approach in handling respiratory problems in COPD patients.